2019
DOI: 10.1017/s0007114519002241
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews and meta-analysis in nutrition research

Abstract: There exists an ever-increasing number of systematic reviews, with or without meta-analysis, in the field of nutrition. Concomitant with this increase is the increased use of such to guide future research as well as both practice and policy-based decisions. Given this increased production and consumption, a need exists to educate both producers and consumers of systematic reviews, with or without meta-analysis, on how to conduct and evaluate high-quality reviews of this nature in nutrition. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 120 publications
0
24
0
Order By: Relevance
“…This systematic review followed the protocol of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (45) and the methodology suggested by the Academy of Nutrition and Dietetics for the evidence analysis process in 2016 (46) is shown in Table 1 (44) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review followed the protocol of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (45) and the methodology suggested by the Academy of Nutrition and Dietetics for the evidence analysis process in 2016 (46) is shown in Table 1 (44) .…”
Section: Methodsmentioning
confidence: 99%
“…However, to our knowledge, no systematic review to date has compared the relative validity of FFQ in relation with reference methods in children and adolescents. Systematic reviews with meta-analysis have the strength of increased statistical power for primary outcomes, the ability to reach agreement when original studies yield conflicting findings, improving effect size estimates and answering questions not addressed in original trials (44) . Therefore, the aim of the present study was to evaluate the relative validity of FFQ in assessing the dietary intake of children and adolescents, comparing the questionnaire with other forms of evaluating food consumption through a systematic review, considering energy, macronutrients (carbohydrates (CHO), protein, fat and fibre), certain micronutrients (Ca, Fe, Zn, vitamin A and vitamin C) and some food item (meat, milk, fruits and vegetables).…”
mentioning
confidence: 99%
“…The protocol for this review adheres to previously published guidelines [ 43 ] and includes all items described in the checklist of Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) [ 44 ]. The completed checklist is available in Supplementary File 1 , and the protocol for this review was pre-registered in the Open Science Framework Registry ( https://osf.io/6f8dz ).…”
Section: Methodsmentioning
confidence: 99%
“…The degree of heterogeneity of the studies was analyzed through Cochran's Q test [35], and the degree of consistency between studies was calculated through the I 2 test, which was interpreted as low (≤ 25%), moderate (26-74%), and high (≥ 75%) [36]. The effect of the studies with small samples was determined by the Doi plot [33] and the Luis Furuya-Kanamori (LFK) index [33] to detect asymmetry as Egger's regression loses statistical power in small samples [37]. The LFK values outside the interval -1 and 1 were considered consistent with asymmetry (i.e., publication bias) [38].…”
Section: Meta-biasesmentioning
confidence: 99%